2021
DOI: 10.3390/nano11061517
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Transition Metal Dichalcogenide Cathode Materials for Aqueous Rechargeable Multivalent Metal-Ion Batteries

Abstract: The generation of renewable energy is a promising solution to counter the rapid increase in energy consumption. Nevertheless, the availability of renewable resources (e.g., wind, solar, and tidal) is non-continuous and temporary in nature, posing new demands for the production of next-generation large-scale energy storage devices. Because of their low cost, highly abundant raw materials, high safety, and environmental friendliness, aqueous rechargeable multivalent metal-ion batteries (AMMIBs) have recently gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 153 publications
(194 reference statements)
0
30
0
Order By: Relevance
“…The overall structure and methodol- TMDs monolayers are atomically thin (~6 to 7 Å) semiconductors consisting of type MX 2 , where M is a transition metal atom from IVB-VIB (Ti, Zr, Hf, V, Nb, Ta, Mo, Tc, W, Re, Co, Ni, Rh, Ir, Pt or Pd) and X is a chalcogen atom (S, Se or Te). Hence, they are considered analogs of graphene with a layered structure [65]. Importantly, the bandgap is a critical characteristic of TMDs that influences transistor on/off ratio and chemical stability and durability in ambient conditions.…”
Section: Types Of Elements As the Critical Parameters For Biocompatible Sensorsmentioning
confidence: 99%
“…The overall structure and methodol- TMDs monolayers are atomically thin (~6 to 7 Å) semiconductors consisting of type MX 2 , where M is a transition metal atom from IVB-VIB (Ti, Zr, Hf, V, Nb, Ta, Mo, Tc, W, Re, Co, Ni, Rh, Ir, Pt or Pd) and X is a chalcogen atom (S, Se or Te). Hence, they are considered analogs of graphene with a layered structure [65]. Importantly, the bandgap is a critical characteristic of TMDs that influences transistor on/off ratio and chemical stability and durability in ambient conditions.…”
Section: Types Of Elements As the Critical Parameters For Biocompatible Sensorsmentioning
confidence: 99%
“…In general, in layered TMDC materials, the defective sites are very active and absorb the site for foreign ions while minimizing the stress and electrostatic force among the layers, which can enhance the diffusivity and reduce the transportation paths in the hierarchical porous structure. 40,41 Herein, the appeared lattice defects and synergistic effect in the unique mixedphase NMS/NS@CC-210 heterostructure promoted the larger electrochemical active sites, enhanced the diffusivity of OH-electrolyte ions, and shortened the electron transportation paths. The optimized NMS/NS@CC-210 electrode showed improved reaction kinetics, rate capability, and cyclability compared to the other two MS@CC-210 and NS@CC-210 electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the mixed‐phase NMS/NS@CC‐210 sample consisting of plenty of defective lattice sites in its hierarchical flower‐like nanostructures was noticed. In general, in layered TMDC materials, the defective sites are very active and absorb the site for foreign ions while minimizing the stress and electrostatic force among the layers, which can enhance the diffusivity and reduce the transportation paths in the hierarchical porous structure 40,41 . Herein, the appeared lattice defects and synergistic effect in the unique mixed‐phase NMS/NS@CC‐210 heterostructure promoted the larger electrochemical active sites, enhanced the diffusivity of OH– electrolyte ions, and shortened the electron transportation paths.…”
Section: Introductionmentioning
confidence: 99%
“…M and X represent transition metal and chalcogen atom, respectively. Since the chalcogen atoms are saturated and the molecular interlayer force of the TMD material is weak, few-layer TMD can be obtained by mechanical exfoliation, vapor deposition methods, etc. Due to the interlayer isolation of TMDs, 2D TMDs exhibit better properties than 3D TMDs, facilitating their potential advantages in electronics, photonics, biomedicine, and sensor. For instance, Avdizhiyan et al created photodetectors (PDs) based on two-dimensional TMD alloys and showed that the spectral sensitivity of the created PDs can be significantly altered by changing the composition of TMD . Zhang et al have demonstrated that monolayer TMD nanosheets (NSs), including MoS 2 , TiS 2 , and TaS 2 , can serve as a sensing platform for DNA fluorescence detection, and they have been successfully used for multiplex detection of DNA …”
Section: Introductionmentioning
confidence: 99%